2021
DOI: 10.3390/life11040314
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A, Bisphenol F, and Bisphenol S: The Bad and the Ugly. Where Is the Good?

Abstract: Background: Bisphenol A (BPA), a reprotoxic and endocrine-disrupting chemical, has been substituted by alternative bisphenols such as bisphenol F (BPF) and bisphenol S (BPS) in the plastic industry. Despite their detection in placenta and amniotic fluids, the effects of bisphenols on human placental cells have not been characterized. Our objective was to explore in vitro and to compare the toxicity of BPA to its substitutes BPF and BPS to highlight their potential risks for placenta and then pregnancy. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 62 publications
3
28
0
Order By: Relevance
“…To perform our study, we selected a human placental model, the JEG-3 cells, as we previously demonstrated that JEG-Tox cells can be of great value in placental toxicology studies [ 28 ]. We demonstrated in our previous work in these cells that the activation of the P2X7 receptor is a marker of placental toxicity including endocrine-disrupting chemical-induced toxicity, as we highlighted that the well-known endocrine-disrupting chemicals known as bisphenol A or diethylstilbestrol, despite their chemical differences, shared a common mechanism: the activation of the P2X7 degenerative receptor in human placental cells [ 25 , 26 , 27 ]. Our results showed an activation of the P2X7 degenerative receptor induced by non-cytotoxic concentrations of forskolin from 1µM, demonstrating a placental toxicity of forskolin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To perform our study, we selected a human placental model, the JEG-3 cells, as we previously demonstrated that JEG-Tox cells can be of great value in placental toxicology studies [ 28 ]. We demonstrated in our previous work in these cells that the activation of the P2X7 receptor is a marker of placental toxicity including endocrine-disrupting chemical-induced toxicity, as we highlighted that the well-known endocrine-disrupting chemicals known as bisphenol A or diethylstilbestrol, despite their chemical differences, shared a common mechanism: the activation of the P2X7 degenerative receptor in human placental cells [ 25 , 26 , 27 ]. Our results showed an activation of the P2X7 degenerative receptor induced by non-cytotoxic concentrations of forskolin from 1µM, demonstrating a placental toxicity of forskolin.…”
Section: Discussionmentioning
confidence: 99%
“…The choriocarcinoma-derived JEG-3 cell-line (ATCC HTB-36, Manassas, VA, USA), was selected based on the results of previous studies highlighting the use of these endocrine cells for placental toxicity studies [ 25 , 26 , 27 , 28 ]. JEG-3 cells were cultured in Minimum Essential Medium Eagle’s medium supplemented with 10% FBS, 2 mM of glutamine, 50 U/mL of penicillin and 50 µg/mL of streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the toxicity of other alternative compounds of this group, such as bisphenol-F (BPF) and bisphenol-S (BPS), and 3,3′,5,5′-tetrabromobisphenol-A (TBBPA) that are also used as a flame retardant, are being investigated. Further, several studies have revealed that these compounds also presented toxicity in specific BPF and BPS ( Fouyet et al, 2021 ).…”
Section: Pathways Of Plastic Additive Toxicitymentioning
confidence: 99%
“…The hPlacentox assay, selected by the public–private PEPPER platform for the pre-validation of methods for endocrine disruptors characterization, is based on the human placental JEG-Tox cell model and allows the study of not only hormones disruption (both steroids and polypeptides), but also adverse health effects in the same cells [ 17 ], to meet WHO’s definition of EDCs [ 18 ]. Our previous studies in JEG-Tox cells showed that P2X7 receptor activation would be a common cellular mechanism of toxicity for EDCs in placenta [ 19 , 20 ]. P2X7 receptor activation is reported to be involved in multiple pathologies from immune disorders to degenerative diseases and placental disorders [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%